Bayanihan Savings Replication Program an institution-centered approach to social capital - Bendo, Kristinne Ardel S.; Gerez, Maria Arlyn A.; Brazas-Lim, Ladylyn (2016)
Bayanihan Savings Replication Program is a community based savings, finance and enterprise program that builds the capacities of low-income families in handling their finances and managing their livelihood. It also refers to the common practice of a group of people who voluntarily contribute their individual savings to a common fund from which they borrow to meet emergency, unexpected expenses and for livelihood purpose. This practice operates on the basis of trust, cooperation and mutual help. This program was replicated by the city mayor's office of Tacloban City currently spearheaded by the City Housing Department of the Local Government of the said city. The program aims to provide financial access to the member units within communities and strengthen values formation in a post-disaster setting.
This paper focuses on the Institution Centered Approach to Social Capital. This claims that for social capital to flourish, it needs to be embedded in and linked to the political context as well as formal political institutions (Rothstein, 2005). This aims to study the role of formal political and legal institutions in shaping social capital in a post-disaster setting. This research paper is anchored on Paul Collier's definition of governmental social capital which refers to governmental institutions that influence people's ability to cooperate for mutual benefit. In relation to the government social capital is the Bayanihan Savings Replication Program that can be considered as an example of this type of social capital that is embedded in and linked to a formal political institution which is the City Housing Department.
The results of the study revealed that the local government of Tacloban City was able to influence the Bayanihan Savings Replication Program members to cooperate for mutual help. They were able to influence the growth of generalized reciprocity through values formation and the Bayanihan Savings Replication Program was able to provide financial access to the members of the program. The frequency of interactions, homogeinity of the members and hierarchy within the organization through appointing officers in each unit contributed in the maintenance of the program. The role of local government unit was to monitor and arbitrate in any issues concerning the organization. Furthermore, the government was able to gain trust on the members of the organization through the establishment of BSRP. Lastly, an institution-centered approach to social capital is effective for social capital to flourish which is evident in the case of Bayanihan Savings Replication Program.
Undergraduate thesis (B.A.S.S. Political Science ) -- University of the Philippines, Tacloban.
Keywords: Social Sciences